Facile formation of interconnected multi-walled carbon nanotube-graphene nanocomposite for nanoelectronics applications - Kang, C.H. (Trans Tech Publications Ltd, 2017)
Novel nanocomposite made of one-dimensional (1-D) multi-walled carbon nanotube (MWCNT) and two-dimensional (2-D) graphene was prepared. MWCNT was spin coated onto copper foil and followed by chemical vapor deposition (CVD) growth of graphene. The MWCNT-Graphene nanocomposite was transferred onto target substrate by using a standard polymer-based transfer technique. HRTEM and Raman spectroscopy showed high crystallinity of fused MWCNT and graphene layer. Low defect-related D-peak was also observed even after the nanocomposite underwent high temperature processing. As compared to pristine graphene, electrical characterization of MWCNT-Graphene nanocomposite also revealed the reduction of sheet resistance by ∼71 and almost 2-fold improvement in room-temperature carrier mobility. These improvements are surmised due to additional conducting channels formed by MWCNT in the graphene layer. Hence, higher electrical conductivity can be expected. With the introduction of MWCNT across the graphene layer, highly desirable electrical properties can be achieved and as such leveraging the viability of graphene-based nanoelectronics devices. © 2017 Trans Tech Publications, Switzerland.